A Convenção de Viena sobre contratos de compra e venda internacional de mercadorias e o papel do Estado no projeto de uniformização do Direito Privado Internacional - Bertotti, Daniela (2017)
The present study aims at analyzing the United Nations Convention on Contracts for the International Sale of Goods (CISG) by examining most thoroughly the different interpretations of its text on the light of several western legal traditions. This analysis of the implications of such different interpretations will give rise to a discussion on the level of interpenetration among different legal systems. This, in turn, leads to an analysis of the impact of the conditions imposed by the Convention on its interpretation, which is considered a selfcontained autonomous ruling within the text of the Convention. As can be seen from a historical overview of the matter, the pursuit of unified regulations governing the international purchase and sale of goods is precisely the result of trade practices and of the consolidation of customary laws and principles. This thesis is thus based on the dynamics of this unifying process. The analysis will focus on its innovative feature of a consonant interpretation; an important structural element which may determine the success or failure of the text of the Convention when observed in different legal environments. It will be taken into consideration the role of the relation between governments and their institutions established with International Organizations, as well as that of the need for predictability when signing international agreements. Therefore, elements such as sovereignty and globalization are essential for a proper understanding of the impacts of this Convention in international law, namely, international trade laws